2011
DOI: 10.3168/jds.2010-3788
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation of toll-like receptor genes and infection by Mycobacterium avium ssp. paratuberculosis in Holstein-Friesian cattle

Abstract: Toll-like receptors (TLR) are membrane proteins that play a key role in innate immunity, by recognizing pathogens and subsequently activating appropriate responses. Mutations in TLR genes are associated with susceptibility to inflammatory and infectious diseases in humans. In cattle, 3 members of the TLR family, TLR1, TLR2, and TLR4, are associated with Mycobacterium avium ssp. paratuberculosis infection, although the extent of this association for the TLR1 and TLR4 receptors has not yet been determined. Moreo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 49 publications
3
36
6
Order By: Relevance
“…This variant (G) was also predominant in a Canadian Holstein bull population studied by Sharma et al (2006), who also found an association between the C allele, higher SCS, and higher lactation persistence. This SNP has also been implicated in the susceptibility to paratuberculosis (Ruiz-Larrañaga et al, 2011). Although SCS has previously been genetically correlated with clinical mastitis (albeit not definitively) and has been used as an indicator of mastitis and exploited for selecting animals with mastitis resistance (Koivula et al, 2005), no association between SCS and genotype or sanitation status was found in our analyses.…”
Section: Genotypingcontrasting
confidence: 53%
“…This variant (G) was also predominant in a Canadian Holstein bull population studied by Sharma et al (2006), who also found an association between the C allele, higher SCS, and higher lactation persistence. This SNP has also been implicated in the susceptibility to paratuberculosis (Ruiz-Larrañaga et al, 2011). Although SCS has previously been genetically correlated with clinical mastitis (albeit not definitively) and has been used as an indicator of mastitis and exploited for selecting animals with mastitis resistance (Koivula et al, 2005), no association between SCS and genotype or sanitation status was found in our analyses.…”
Section: Genotypingcontrasting
confidence: 53%
“…Since the characterization of this PTB form is most closely related to those forms of infection which include shedding MAP in feces and testing positive to the ELISA test [25], one could assume a relative similarity to those animals defined as cases in our previous studies [58] and therefore expect to confirm those already associated SNPs. In this sense, several causes could explain the lack of positive association results on this occasion.…”
Section: Discussionmentioning
confidence: 94%
“…In this sense, several causes could explain the lack of positive association results on this occasion. As mentioned above, our preliminary case-control association studies aimed to identify genetic variations related to microbiological and/or immunological evidences of infection [58], while, in this paper, histopathological observation was used for determining the phenotypical categories. Additionally, in those previous works phenotypical classification strongly leaned on classifying as uninfected controls only those animals that had tested negative in microbiological and immunological diagnostic methods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutations of the TLR system are associated with increased sensitivity to infection by M. avium subsp. paratuberculosis (20,21). Altered levels of TLR expression during natural M. avium subsp.…”
mentioning
confidence: 99%